ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DANA DESA DI DESA SEMANGKO KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA TAHUN 2019 - Nurhasima; Agus Riyanto (University of Widya Gama Mahakam Samarinda, 2021)
This research aims to determine whether the financial management in Semangko Village, Marangkayu District, Kutai Kartanegara Regency has fulfilled the principles of Accountability and Transparency in Village Financial Management. This research uses qualitative research methods with data reduction techniques, data presentation, data conclusion, verification and final conclusions. The data collection techniques used in this field research are interview, observation and document study. The results of data analysis from the results of interviews, observations and document studies on the level of accountability and transparency in the financial management of village funds in Semangko Village, show that the application of Accountability and Transparency in Village Financial Management in Semangko Village, Marangkayu District, Kutai Kartanegara Regency in planning, implementation, administration and the responsibility is good enough